Joining forces to build up knowledge in health promotion: lessons from a French coalition initiative. (30th September 2020) - Porcherie, M; Laurent, A; Ferron, C; ,; Berry, P; Soudier, B; Georgelin, B; Gaspard, S; Berdougo, F; Lombrail, P
Abstract: Issue: French public health authorities increasingly rationalize access to public funding, favoring evidence-based programs. Health Promotion (HP) interventions are especially urged to prove their efficiency in this context. To tackle this issue, HP practitioners hold experiential knowledge (EK) that proves useful to assess both the complexity and efficiency of HP interventions. United by this conviction in a multidisciplinary coalition, HP experts from various backgrounds came together five years ago to promote Experiential Knowledge in HP (EKHP) in France. A national committee to promote EKHP 670 HP practitioners were surveyed in 2016. Results reported vast amounts of under-documented and often untapped field expertise in HP and numerous obstacles regarding access to scientific literature or systematic reviews. Consequently, the coalition launched a National Committee for EKHP, meeting 5 times a year since 2016. Members of 6 national HP organizations, of 4 regional HP institutes, national and local public health administrators, researchers, consultants and field workers participate. Steered by the French Society for Public Health and the National Federation for Health Education and Promotion, the committee devised a threefold action plan: 1/ advocate EKHP in all relevant institutional spaces, 2/ develop tools for EKHP, 3/ mobilize for EKHP at the local level. Results: The committee designed a method for capitalizing, collecting and circulating EK and published in 2020 a guidebook and a toolkit. French Public Health authorities agreed to share EK nationwide on their online portal. Dissemination within the French HP community has started, through the committee members' networks, and will be amplified with a training program launched in 2021 at the National School of Public Health. Lessons: Attention must be brought to HP practitioners' experiential knowledge, both to recognize HP practitioners' expertise and to help improve the understanding of how HP interventions work. Key messages: Experiential knowledge in HP remains undervalued and untapped in France. Dedicated practitioners, policymakers and researchers formed a multidisciplinary committee to promote and disseminate EKHP. A multilevel strategy combining advocacy and tool building can be effective at promoting experiential knowledge. A multidisciplinary coalition provided the necessary context-specific levers in France.